(untitled) (The Research of Medical Science Review, 2025)
Nursing education is generally comprised of theory and practice. Both clinical teaching and learning are essential parts of nursing education. Objective: The study's objectives are to assess the challenges faced by undergraduate nursing students in the classroom and clinical environment in public and private institutes in Karachi. Methods: This comparative cross-sectional study was carried out in one private and one public sector institution. BS nursing students enrolled in Year -II, Year -III, and Year- IV were included in the study. Statistical significance was set at p < .05. To compare clinical and institutional challenges faced by undergraduate nursing students in Public and Private Sector Institutions, non-parametric independent samples Mann-Whitney test was used. Results: Out of 326 participants, there was a slightly higher proportion of females (55.42%) than males (44.38%) at the public sector institutes. 60.2% of students indicated that inadequate skills training at the institute needed to be improved. Moreover, a significant section of 60.2% noted that the curriculum's clinical placement objectives did not align with hospital job responsibilities. Students of the public sector raised more vital concerns regarding the capability of clinical preceptors and the readiness of clinical instructors. Conclusion: The study determined the problems faced by nursing students in their classroom and clinical settings have a detrimental impact on the learning process.